Acceso al crédito y situación socioeconómica de los beneficiarios del Bono de Desarrollo Humano - Vire Piedra, María Salomé (2023)
The Human Development Bond is a social policy implemented since 1998 as a subsidy that fulfills the purpose of reducing poverty and extreme poverty in Ecuador. As well as to encourage the progress of the beneficiaries, in the year 2007, the Human Development Credit was established, which allows low-income families to undertake and thus improve their socio-economic situation. The present research has as its purpose to evaluate access to credit and the socioeconomic situation of the beneficiaries of the Human Development Bond. For this, it was carried out a study of sort exploratory, descriptive and correlational, using a survey as a data collection instrument applied to a sample of 195 beneficiaries of the Human Development Bonus, belonging to the urban parish El Valle, in the canton of Loja. The results indicate that the majority of people who access the CDH are mothers between 31 and 40 years of age, same that are married and have on average up to 3 family burdens, in the aspect related to entrepreneurship, the results showed that most of the investment was in animal husbandry. However, due to ignorance and lack of technical advice in the financial and productive field, they have not obtained the expected results; the main findings show that the socioeconomic situation of users does not improve with access to the HRC. In this regard, strategies based on the FODA analysis are proposed to help optimize their standard of living and that of their families, including the MIES as a Government Institution. Therefore, it is concluded that the Human Development Credit does not contribute to strengthening the socioeconomic situation of the beneficiaries.